The Life-cycle Benefits of an Influential Early Childhood Program - Jorge Luis García; James J. Heckman; Duncan Ermini Leaf; Maria José Prados (Institute of Labor Economics (IZA), 2016)
This paper estimates the long-term benefits from an influential early childhood program targeting disadvantaged families. The program was evaluated by random assignment and followed participants through their mid-30s. It has substantial beneficial impacts on health, children's future labor incomes, crime, education, and mothers' labor incomes, with greater monetized benefits for males. Lifetime returns are estimated by pooling multiple data sets using testable economic models. The overall rate of return is 13.7% per annum, and the benefit/cost ratio is 7.3. These estimates are robust to numerous sensitivity analyses.
Keywords: J13; I28; C93; 330; childcare; early childhood education; long-term predictions; gender differences in responses to programs; health; quality of life; randomized trials; substitution bias